Production systems design : a product oriented approach and methodology - Alves, Anabela Carvalho (2008)
Production systems design is critical to achieving manufacturing performance and objectives. Although generic approaches to this design are available they may not be able to objectively address specific manufacturing configurations. Here it is argued that product oriented manufacturing (POM) organization offers advantages in relation to the function oriented one. Based on this, a methodology specially addressing POM systems design, and prototype of a Computer Aided Design System based on the methodology were develop. A brief description of both is presented.